New horizons in the treatment of some eye diseases - Roca-Fernández, José Antonio (2019)
In recent years ophthalmology has made significant progress thanks to technology. Corneal transplantation was needed to treat Fuchs' dystrophy, today there is a new treatment modality called descemetorhexis, which has a very high success rate and does not require transplantation. As regard to cataract surgery and the implantation of intraocular lenses, the lenses have progressed amazingly, and can currently achieve almost perfect vision after surgery. With regard to the treatment of some inherited retinal diseases, which were until recently intractable, we have today gene therapy that can stop and inclusive reverse vision loss.